Medico-social profile of male alcoholics in a north Indian city - Mukhopadhyay, J. (International Journal Of Community Medicine And Public Health, 2017)
Background:Alcohol Dependence has been posing an unprecedented public health challenge in recent years. Alcohol related morbidity and mortality has attained new zenith that merits attention. Considering the abominable effects of alcoholism, it was decided to study the medico-social profile of male alcoholics in an urban set-up to identify the risk factors and suggest preventive measures. Methods:60 subjects reporting to a de-addiction centre at a north Indian town for treatment were studied during September 2014-February 2015. All the individuals were satisfying the criteria of alcohol dependence as per diagnostic and statistical manual of mental disorder. A pretested structured proforma was introduced to the consenting individuals, which included demographic details, personal and family history with details of physical and mental status examination. Data obtained was analysed and tabulated. Results:The mean age of the alcoholics seeking treatment was 37.86 years. Majority of them were married, middle school educated, employed urbanite, unskilled workers from lower middle class background. Mean ages of first alcoholic drink and first intoxication were 18.95 and 20.35 years respectively. Dependency developed at 28.60 years. Alcoholic father (65%) and brothers (31.67%) appeared tended the subjects towards alcohol. Financial stress and withdrawal problems mostly steered them to seek treatment. Epidemiological insight unveiled many risk factors like vulnerability of adolescents, male sex, nominal schooling, low socio-economic lineage, early employment, peer pressure, alcoholic father and siblings, financial stress and family discord. Conclusions:More community based studies are suggested to identify the community specific risk factors for alcoholism and recommend suitable preventive measures to abate alcoholism.